Pengaruh Arus Kas Operasi Dan Laba Akuntansi Terhadap Return Saham Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020 - Muhammad Rivandi; Nur Hikmah Lestari (IAIN Madura, 2022)
Stock return is the profit obtained from the investor's share ownership on the investment made. The purpose of this study is to determine the effect of operating cash flow on stock returns of LQ45 companies listed on the Indonesia Stock Exchange in 2018-2020. The research population is all LQ45 companies listed on the IDX. The sample in this study were 23 companies selected by purposive sampling method. The analytical method used is the panel regression method. Based on the hypothesis the research result indicate that operating cash flowh has no effect on stock returns and accounting profit has a positive and significant effect on stock returns